2022
DOI: 10.1128/aac.00269-22
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Autophagy-Related Mechanism of Chloroquine Drug Resistance in the Malaria Parasite

Abstract: We generated highly chloroquine (CQ)-resistant (ResCQ) Plasmodium yoelii parasites by stepwise exposure to increasing concentrations of CQ and CQ-sensitive parasites (SenCQ) by parallel mock treatments. No mutations in genes that are associated with drug resistance were detected in ResCQ clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Though we have only evaluated the level of BiP mRNA, the upregulation in its expression can still be considered as an indicator of ER stress in Pbtmem33(−) parasites (Figure S2b). Since ER stress results in the activation of ERAD and UPR, which in turn regulates cell death pathways like apoptosis and autophagy (Peng et al., 2021), we checked the mRNA expression of autophagy (ATGs) and apoptosis (metacaspases) related genes (Kamil et al., 2019; Kamil, Atmaca, et al., 2022; Vandana et al., 2019). Our preliminary qPCR data showed that TMEM33 deletion results in the generation of ER stress which upregulated the expression of autophagy‐related genes in the malaria parasites (Figure S2c); however, no effect was observed in the expression of apoptosis marker genes (Figure S2d).…”
Section: Discussionmentioning
confidence: 99%
“…Though we have only evaluated the level of BiP mRNA, the upregulation in its expression can still be considered as an indicator of ER stress in Pbtmem33(−) parasites (Figure S2b). Since ER stress results in the activation of ERAD and UPR, which in turn regulates cell death pathways like apoptosis and autophagy (Peng et al., 2021), we checked the mRNA expression of autophagy (ATGs) and apoptosis (metacaspases) related genes (Kamil et al., 2019; Kamil, Atmaca, et al., 2022; Vandana et al., 2019). Our preliminary qPCR data showed that TMEM33 deletion results in the generation of ER stress which upregulated the expression of autophagy‐related genes in the malaria parasites (Figure S2c); however, no effect was observed in the expression of apoptosis marker genes (Figure S2d).…”
Section: Discussionmentioning
confidence: 99%